Pengaruh Profitabilitas, Leverage, Dan Likuiditas Terhadap Ketepatan Waktu Penyajian Laporan Keuangan Pada Perusahaan Subsektor Perdagangan Eceran yang Terdaftar Di Bursa Efek Indonesia Tahun 2015-2019 - Reza Budi Pratomo; Munari (Universitas Sains dan Teknologi Komputer, 2021)
The purpose of this research is to test and prove the factors that influence the timeliness of the company's financial reporting. The variables used in this study are profitability, leverage, and liquidity as independent variables, while the timeliness of the presentation of financial statements as the dependent variable. The population in this case research is a retail trade sub-sector company registered in Indonesia Stock Exchange 2015-2019. This study uses secondary data obtained from www.idx.co.id and related company websites. The data taken is company data for the 2015-2019 period with using purposive sampling, so that the total sample obtained is 7 companies. The analysis technique in this research is multiple linear regression analysis using SPSS 25 software. The results showed that profitability and leverage did not affect the timeliness of the presentation of financial statements, while liquidity affects the timeliness of financial statement presentation.